Study of glycyrrhizic acid contents from Glycyrrhiza glabra populations in Iran and their relation with environmental factors - SHAGHAYEGH REZAEI; TAHER NEJADSATTARI; MOSTAFA ASSADI; RAMEZAN ALI KHAVARINEJAD; IRAJ MEHREGAN (Society for Indonesian Biodiversity, 2017)
Abstract.Rezaei S, Nejadsattari T, Assadi M, Khavarinejad RA,Mehregan I. 2017. Study of glycyrrhizic acid contents from Glycyrrhiza glabra populations in Iran and their relation with environmental factors. Biodiversitas 18: 212-220. Glycyrrhizin (glycyrrhizic acid) is an important chemical composition of licorice (Glycyrrhiza glabra L.) from which is 50 times sweeter than sucrose. In this study, the amount of glycyrrhizic acid was determined in populations collected from 11 different locations in Iran (NW to NE) by HPLC method from two varieties of this species; Glycyrrhiza glabra varieties glabra and glandulifera. Our results showed the highest content of glycyrrhizic acid was from Naghadeh (NAQ, NW Iran) population for G. glabra var. glandulifera and Azadshahr population (AZD, NW Iran ) for G. glabra var. glabra. Lowest amounts of glycyrrhizic acid were detected in Jajrood (JAD, N Iran) population for G. glabra var. glandulifera and Hashtrud (HSD, N Iran) population for G. glabra var. glabra. Significant correlations were observed between the amount of glycyrrhizic acid and some morphometric parameters, soil and environmental factors. The amount of glycyrrhizic acid showed positive correlation with phosphorous (P ≤ 0.05 and R2 =0.155) and negative correlation with pH (P ≤ 0.01 and R2 =0.348) and calcium carbonate (P ≤ 0.01 and R2 =0.507). Higher temperature resulted in increasing the amount of glycyrrhizic acid. Based on morphometrical data, the plants with thinner rhizomes would have more glycyrrhizic acid. Our results also showed that glycyrrhizic acid content was not related to taxonomic classification of this species. Keywords: Ecological factors, glycyrrhizic acid, HPLC, licorice